Formalization beckons: a baseline of informal recycling work in Buenos Aires, 2007–2011. (October 2013) - Parizeau, Kate
The work of Buenos Aires' cartoneros (informal recyclers) has important environmental and economic repercussions for the city. This paper investigates cartoneros ' working and living conditions, establishing a 2007 baseline for the logistics of informal recycling practice in Buenos Aires and providing a description of the socioeconomic characteristics of these workers at a key moment in time. Under the purview of a new chief of government elected in 2007, a formalization plan for cartoneros was initiated in 2011. This paper assesses some of the potential impacts of this plan on cartoneros and their work, and suggests that while such a system may benefit some workers (providing them with increased income, social acceptability and improved relationships with the municipality), there are also potential drawbacks to the formalization plan (including possible difficulties instituting a cooperative system with previously unorganized workers and the labour exclusion of more socially marginalized cartoneros ).